Synergistic insights into human health from aptamer- and antibody-based proteomic profiling - Maik Pietzner (Nature Portfolio, 2021)
Broad-capture affinity-based proteomic technologies inform how the readout of our genes affects human health. Here, the authors integrate aptamer- and antibody-based profiling to understand the mechanisms underlying gene-protein-disease associations.